A laminin-based local regulatory network in the testis that supports spermatogenesis. (January 2022) - Bu, Tiao; Wang, Lingling; Wu, Xiaolong; Li, Linxi; Mao, Baiping; Wong, Chris K.C.; Perrotta, Adolfo; Silvestrini, Bruno; Sun, Fei; Cheng, C. Yan
Abstract: In adult rat testes, the basement membrane is structurally constituted by laminin and collagen chains that lay adjacent to the blood-testis barrier (BTB). It plays a crucial scaffolding role to support spermatogenesis. On the other hand, laminin-333 comprised of laminin-α3/ß3/γ3 at the apical ES (ectoplasmic specialization, a testis-specific cell-cell adherens junction at the Sertoli cell-step 8–19 spermatid interface) expressed by spermatids serves as a unique cell adhesion protein that forms an adhesion complex with α6ß1-integrin expressed by Sertoli cells to support spermiogenesis. Emerging evidence has shown that biologically active fragments are derived from basement membrane and apical ES laminin chains through proteolytic cleavage mediated by matrix metalloproteinase 9 (MMP9) and MMP2, respectively. Two of these laminin bioactive fragments: one from the basement membrane laminin-α2 chain called LG3/4/5-peptide, and one from the apical ES laminin-γ3 chain known as F5-peptide, are potent regulators that modify cell adhesion function at the Sertoli-spermatid interface (i.e., apical ES) but also at the Sertoli cell-cell interface designated basal ES at the blood-testis barrier (BTB) with contrasting effects. These findings not only highlight the physiological significance of these bioactive peptides that create a local regulatory network to support spermatogenesis, they also open a unique area of research. For instance, it is likely that several other bioactive peptides remain to be identified. These bioactive peptides including their downstream signaling proteins and cascades should be studied collectively in future investigations to elucidate the underlying mechanism(s) by which they coordinate with each other to maintain spermatogenesis. This is the goal of this review.